Feedforward and feedback active control of metro pantographs under abnormal excitations due to track conditions - YANG Gang; KONG Guowei; SHEN Xin (机车电传动)
Metros are predominantly equipped with low-elasticity overhead rigid catenaries, which can easily lead to poor pantograph-catenary relationship. In recent years, abnormal wear has occurred frequently between the pantographs and catenaries in metro systems, but feasible suppression methods are still lacking due to an unclear mechanisms behind this wear. Metro trains often undergo vertical vibrations with relatively large amplitudes, particularly in areas affected by abnormal track conditions, such as track bed settlement, intersections with roads, irregularities at rail joints, and small vertical curves. These intense vibrations impose significant excitations on the pantographs, resulting in sharp changes in contact force of the pantograph-catenary, which leads to declines in the current-receiving quality of the pantograph-catenary systems and contributes to abnormal wear of the carbon contact strips. In the present study, a dynamics model was constructed to simulate rigid catenary-pantograph systems on metros. The influence of abnormal track excitations on the current-receiving quality of pantographs was analyzed through numerical calculations method. Additionally, feedforward/feedback control strategies were designed for pantographs. A comparative analysis was then conducted to evaluate the effects of several specific control techniques on the current-receiving quality of pantographs, including feedforward control, fuzzy feedback control, and feedforward/feedback integrated control. The results show that: (1) Abnormal track excitations significantly affected the degree of fluctuations in pantograph-catenary contact forces; (2) The feedforward control strategy accurately and effectively compensated for abnormal track excitations; and (3) The feedforward/feedback integrated control effectively reduced the degree of fluctuations in pantograph-catenary contact forces, thereby effectively improving the quality of current-receiving through pantograph-catenary contact while inhibiting mechanical and electrical wear in the pantograph-catenary systems.